Faktor-Faktor yang Mempengaruhi Pengungkapan Akuntansi Sumber Daya Manusia pada Perusahaan Perbankan di Indonesia Periode 2016-2018 - Nur Afni Yunita; Yuni Mauliza (Forum Inovasi Bisnis dan Manajemen, 2020)
This study aims to determine the effect of profitability, product diversification, concentration of share ownership and institutional ownership on the disclosure of human resource accounting in banking companies in Indonesia. The number of samples used in this study were 20 companies with a total of 60 data. The data analysis technique used is multiple linear regression analysis. The partially results showed are the variables of profitability, concentration of share ownership and institutional ownership had no effect on disclosure of human resource accounting. Meanwhile, the product diversification variable has significant effect on human resource accounting disclosure